Effect of exergy optimisation on a cogeneration system's CO2 emissions according to different demand patterns. (6th May 2008) - Fonseca Junior, Joao Gari da Silva; Asano, Hitoshi; Fujii, Terushige; Hirasawa, Shigeki
The objective of this work is to verify how different operational strategies affect the CO2 emissions of a cogeneration system according to different demand patterns. The operation strategies studied were focused in running cost and exergetic efficiency. The results show that the optimal exergetic efficiency strategy generated the highest emissions reduction. The operation with the highest average ratio between heat and power loads presented the best reduction of CO2 emissions, around 13%. Minimising the running cost reduced CO2 emissions in 11.7% for the highest average heat and power ratio demand whereas for the lowest ratio the emissions increased 24.3%.